Does the digital economy exhibit multiplier effects? A case study on the optimization of agricultural production structure in rural digital economy - Fengting Wang; Hao Wang; Lichun Xiong (International Journal of Agricultural Sustainability)
The multiplier effect of the digital economy exists in production activities, so is the structure of agricultural production, which is closely related to it, affected by the digital economy? Based on the panel data of 30 provinces from 2011 to 2020. The results show that: (1) The development level of China's rural digital economy shows a general upward trend, showing regional differences with high levels in the southeastern coastal regions and low levels in the central and western regions. (2) The rural digital economy significantly contributes to agricultural production structure upgrading (APSU), this positive effect is more obvious in the main grain-producing areas, areas with a high degree of land transfer, and agricultural production agglomeration areas. (3) The rural digital economy achieves APSU by promoting technological innovation, facilitating industrial integration, and stimulating consumption upgrading, while there is a multiplier effect for this impact, that is, the existence of Metcalfe's law in APSU was verified for the first time. The multiplier effect stems not only from the rural digital economy, but also from the synergistic effect formed by technological innovation, industrial integration, and consumption upgrading, jointly playing a role in increasing marginal effects.